The global role, impact, and limitations of Community Health Workers (CHWs) in breast cancer screening: a scoping review and recommendations to promote health equity for all (2021)
Introduction: Innovative interventions are needed to address the growing burden of breast cancer globally, especially among vulnerable patient populations. Given the success of Community Health Workers (CHWs) in addressing communicable diseases and non-commu-nicable diseases, this scoping review will investigate the roles and impacts of CHWs in breast cancer screening programs. This paper also seeks to determine the effectiveness and feasi-bility of these programs, with particular attention paid to differences between CHW-led interventions in low- and middle-income countries (LMICs) and high-income countries (HICs). Methods: A scoping review was performed using six databases with dates ranging from 1978 to 2019. Comprehensive definitions and search terms were established for ‘Community Health Workers’ and ‘breast cancer screening’, and studies were extracted using the World Bank definition of LMIC. Screening and data extraction were protocolized using multiple independent reviewers. Chi-square test of independence was used for statistical analysis of the incidence of themes in HICs and LMICs. Results: Of the 1,551 papers screened, 33 were included based on inclusion and exclusion criteria. Study locations included the United States (n=27), Bangladesh (n=1), Peru (n=1), Malawi (n=2), Rwanda (n=1), and South Africa (n=1). Three primary roles for CHWs in breast cancer screening were identified: education (n=30), direct assistance or performance of breast cancer screening (n=7), and navigational services (n=6). In these roles, CHWs improved rates of breast cancer screening (n=23) and overall community member knowledge (n=21). Two studies performed cost-analyses of CHW-led interventions. Conclusion: This review extends our understanding of CHW effectiveness to breast cancer screening. It illustrates how CHW involvement in screening programs can have a significant impact in LMICs and HICs, and highlights the three CHW roles of education, direct perfor-mance of screening, and navigational services that emerge as useful pillars around which governments and NGOs can design effective programs in this area.